Sustainable textiles life cycle and environmental impact - Blackburn, R. S. (Woodhead ; CRC Press, 2009)
Annotation The global textile industry, like many others is inherently unsustainable, and has a high impact upon the environment. The cotton industry alone is a major user of synthetic fertilisers and pesticides. The industry also consumes large amounts of water, putting pressure on scarce water resources and the environment. This book will investigate the entire life cycle of textiles and their impact on the environment. Chapters will analyse all stages of the textile industry beginning with the production and manufacture of fibres, through to fabric manufacture and the final recycling of textiles. A concluding set of chapters will examine sustainable environmental applications and case studies within the textile industry.
Published in association with the Textile Institute.
Keywords: Textile industry -- Environmental aspects.; Textile fabrics -- Environmental aspects.; Sustainable development.; Product life cycle.; elektronické knihy; electronic books